Surviving Change: a Manager's Guide: Essential Strategies for Managing in a Downturn - Harvard Business School Publishing Corporation (Harvard Business School Press, 2009)
Today's constantly changing environment makes many managers stop in their tracks. With so much uncertainty, how will you (and your company) get through it? You've got to take action, and with confidence. This book gives you the essential tools you need to get through these turbulent times.